Linear Non-Threshold: Separating Facts from Fiction - A. Alan Moghissi; Betty R. Love; Sorin R. Straja (SAGE Publishing, 2012)
The Linear Non-Threshold (LNT) process is used by virtually all governmental agencies to compute incidence of cancer as a consequence of exposure to a carcinogen. This comment applies the concept of Best Available Science (BAS) Metrics for Evaluation of Scientific Claims (MESC) derived from BAS to issues related to reliability of LNT hypothesis. This paper identifies the level of maturity of the LNT hypothesis and the associated uncertainties.